Investigations of some advanced control strategies for typical and emerging inductive power transfer systems - Sun, Zhen (Nanyang Technological University, 2024)
Inductive power transfer (IPT) is considered to be an effective alternative of batteries to alleviate the hassle of using cables to transmit power in some harsh environments. Typical IPT systems are designed based on advanced technologies of coupled coils, compensated circuits, power electronic driving and rectification circuits, control strategies, electromagnetic compatibility, and other safety considerations. This program focuses on the studies of advanced control strategies for typical and emerging IPT systems. The emerging IPT systems refer to the IPT systems with simplified receiver circuits to cater the emerging IPT standards, such as “Qi2.0”. Specifically, multi-stage conversions at the receiver side are eliminated to ensure higher efficiency, higher power density, and better charging performance. The control strategies are implemented at the transmitter sides, while the receiver sides only maintain the passive components and protections. This new control paradigm shift will benefit the emerging IPT applications with higher power levels, such as the 200 W medium power standard for portable tools and notepads, and up to the 2 kW “Ki” standard for kitchen appliances. This thesis will look back at the classic self-oscillating control for typical IPT systems with load-independent outputs. The dynamic performance and robustness against parameter drifts of the self-oscillating control will be critically reviewed and verified. Besides, a communication-free primary-side current and voltage control scheme is also investigated. The control scheme is established based on a model predictive control and artificial intelligence algorithms to identify the receiver parameters, such that the output voltage and current control can be implemented without any communication feedbacks from the receivers to the transmitters.